Estimation of Composite Plate Attenuation - Svilainis, L.; Rodriguez, A.; Dumbrava, V.; Chaziachmetovas, A.; Eidukynas, V. (Elektronika ir Elektrotechnika, 2014)
A new method based on Ping He’s technique for simultaneous measurement of frequency dependant thickness and attenuation was developed without any need of a priori knowledge of the material parameters. The thickness and attenuation coefficient for longitudinal wave were measured in a thin specimen of glass fiber reinforced plastic produced by Resin Transfer Molding. A 5 MHz pulse of 0.1 µs duration was used as excitation signal. Mean error and standard deviation of the frequency dependant thickness are used to compare both techniques. The new method has demonstrated to be more accurate than conventional Ping He’s technique, and can be implemented automatically thus saving processing time and increasing accuracy. Measurement of the attenuation coefficient is achieved using the frequency dependent thickness without requiring any additional parameter of the material. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.4675